Independent association between serum sclerostin levels and carotid artery atherosclerosis in prevalent haemodialysis patients - Kirkpantur, Alper; Balci, Mustafa; Turkvatan, Aysel; Afsar, Baris (OXFORD UNIV PRESS, 2015)
Background: Sclerostin is a soluble inhibitor of the Wntsignalling pathway and has been shown to be associated with decreased bone turnover and vascular and/or valvular calcification in patients with chronic kidney disease. Common carotid artery intima-media thickness (CIMT) assessment and common carotid artery (CCA) plaque identification with ultrasound imaging are well-recognized tools for the identification and monitoring of atherosclerosis. The aim of the present study was to investigate whether the circulating levels of sclerostin might be associated with carotid artery atherosclerosis in prevalent haemodialysis patients. Methods: In this cross-sectional study, serum sclerostin concentrations were measured using a commercially available enzyme-linked immunosorbent assay kit. CIMT was measured and carotid plaques were identified by B-mode and Doppler ultrasound imaging. Results: One hundred and twenty-two prevalent haemodialysis patients were involved in the study. Serum sclerostin levels were higher in patients with plaques in CCA than patients free of plaques ( 227 +/- 166 versus 117 +/- 91 pmol/L, P = 0.016). A significant correlation was recorded between serum sclerostin levels and CIMT (r = 0.459, P < 0.0001). In the multiple regression analysis, sclerostin concentrations were one of the independent factors that remained significantly associated with CIMT. Conclusion: Sclerostin is independently associated with CIMT although further studies are needed.
Keywords: carotid artery intima-media thickness; haemodialysis; sclerostin